ANALISIS KESALAHAN BERBAHASA DALAM PENULISAN LAMARAN PEKERJAAN SISWA KELAS XII TPM 4 SMK NEGERI REMBANG KABUPATEN PASURUAN TAHUN PELAJARAN 2019/2020 - YUDHA WIDWIARTI (sarasvati, 2020)
This study aims to describe language errors in writing job applications. The method used is descriptive qualitative. In this study, the data collected took the form of the results of writing job applications for class XII TPM 4 VOCATIONAL SCHOOL, Rembang, Pasuruan Regency in the academic year 2019/2020. From the research it can be concluded the error in writing job applications for class XII TPM 4 VOCATIONAL SCHOOL, Rembang, Pasuruan Regency, 2019/2020 academic year. These errors include the use of spelling and punctuation, word choices, and sentence construction